Wine, soil, and salvation in the Hebrew Bible and New Testament - Scarlata, Mark William (Cambridge University Press, 2025)
"Mark Scarlata provides a biblical theology of wine in this volume through exploration of texts in the Hebrew Bible, later Jewish writings, and the New Testament. He shows how wine is intimately connected to soil, humanity, and harmony between humans and the natural world"